Ecotoxicology of Copper in Horticultural Soils: A Review - Elhawat, N.; Alshaal, T. A.; Kratz, S.; Domokos-Szabolcsy, É.; El-Ramady, H. R.; Prokisch, J.; Eszenyi, P.; Sztrik, A.; Babka, B.; Fári, M. G. (International Journal of Horticultural Science, 2013)
Nowadays, the world is facing the problem of environmental pollution because of the increase of man’s needs requires development in life activities, progress industrialization, transportation tools, enhancement of agriculture and exploitation of natural resources. Soil and water resources are extremely exposed to pollution from different aspects. Agrochemicals in particular, have created severe problems, since they release thousands of chemicals to the environment. Several studies on the effect of environmental pollutants on agroecosystem have been carried out. On the other hand, the importance of trace elements as environmental pollutants is well known and well documented in literature. Cu contamination to agricultural soils has been accelerated due to its wide and repeated use in agriculture and horticulture as fertilizers or fungicides to protect vines, citrus trees, and other fruit crops against fungus diseases. Applied Cu from different agrochemical sources to agroenvironment may be adsorbed and are transported to the groundwater table and pollute it besides polluting the soils. The use of Cu-based fungicides in vineyard soils is widely documented worldwide. It has been found that many countries contain concentrations in excess of 100 mg kg−1. Importance of study of transport of Cu arises due to the fact that Cu is absorbed in soils and also reaches the groundwater table, thus polluting both soil and ground water. It is often more important to be able to estimate the mobile fraction, the readily soluble fraction, the exchangeable fraction, or the plant available fraction of Cu content of a soil as a more direct indication of the likelihood of deleterious or toxic effects on soils and groundwater. Therefore, the aim of present work was to highlight the behavior and ecotoxicological effects of copper on horticultural soils.